An Examination of Earnings Quality in Australia : Do Auditor Attributes Matter? - Singh, Abhijeet (Curtin University, 2014)
This study examines the effect of multiple auditor attributes underpinning auditor quality (that is, auditor brand, auditor specialization, provision of non-audit services, and audit partner tenure) on earnings quality across a longitudinal timeframe. The analysis is important given continuing questions and uncertainty of the precise nature of the auditor quality/earnings quality linkage. Results from this study have clear implications for auditors, corporate management/firms, regulators, capital market participants, and scholars alike.